Analysis of the Impact of the Implementation of Local Regulation on Entertainment Tax in Sidenreng Rappang, Indonesia - Hafid, Fadhliah; Ibrahim, Monalisa; Lukman, Lukman (Jurnal Studi Ilmu Pemerintahan, 2023)
This research aims to determine the extent of the implementation of the Sidenreng Rappang District Regulation Number 4 of 2016 concerning Amendments to the Sidenreng Rappang District Regulation Number 22 of 2010 concerning Entertainment Tax in Watang Pulu Sub-District, Sidenreng Rappang District, in terms of policy content and context, using a quantitative descriptive research method with linear regression data analysis technique using SPSS 21 as the analysis tool. Data collection methods include observation, questionnaires, interviews, and literature studies. The sample used was 55 people consisting of night entertainment venue managers and officials from Watang Pulu Sub-District, as well as officials from the village located in Watang Pulu Sub-District. Based on the data processing results, the recapitulation of policy content indicators shows a percentage of 58.42% falling into the category of less good. The recapitulation of policy environment indicators is at a percentage of 54%, which means it falls into the less good category. Meanwhile, the SPSS data processing results show that the validity test of the 10 tested indicators each has a value greater than 0.266, which means that the policy implementation is considered valid. Meanwhile, its reliability has a value of 0.56 > 0.26, which means it is reliable.